DESIGN OF SCREW CONVEYOR MACHINE TO IMPROVE THE EFFECTIVENESS OF SALT FARMERS' WORK - Abdul Majid Budianto (UNIVERSITAS SRIWIJAYA, 2022)
AbstractSalt is one of the complements of food that we often encounter in everyday life. To facilitate in the manufacture of salt, there needs to be automatic tools so as to improve effective work results. Screw Conveyor is one type of material transfer aircraft that is the principle of thread in the process of working with a simple design. Screw conveyor consists of thread pipes arranged on pipes or shafts that rotate in a fixed tube then moved using a motor. Components used in screw conveyors include: electric motors, reducers, shafts, bearings, troughs, and screws. The material used is stainless steel 316L.This research contains the design of screw conveyor machines using autodesk inventor application 2015, in this design the material uses SS316L plates with a thickness of 2 mm, then for frames / frames using elbow iron with a thickness of 4 x 40 mm and 5 x 50 mm. The results obtained from this study are, the capacity obtained is 1711 ft3 / hr. with the number of screw leaves 23, pitch 150, it produces the total power needed to rotate this screw conveyor by 2 HP with an actual conveyor rotation speed of 38.2 rpm.